Re-Evaluating the Chronology of Caracalla's Reign: When Was Caracalla in Nikomedia? - Lindholmer, Mads Ortving (Classica et Mediaevalia, 2022)
It has become increasingly common to assert that Caracalla wintered in Nicomedia in 213/214 rather than 214/215. This is important because it has led scholars to argue that Caracalla’s activities and campaigns in the Balkans are largely invented by ancient historiographers. The present article examines and rejects the evidentiary basis of the new dating and, through an analysis of Caracalla’s itinerary and relevant coinage, provides strong support for the theory that Caracalla wintered in Nicomedia in 214/215. This reconstruction significantly influences the wider chronology of Caracalla’s reign and restores his activities in the Balkans to the history books.